2018
DOI: 10.1007/s11119-018-9582-5
|View full text |Cite
|
Sign up to set email alerts
|

Integration of hydrogeophysical datasets and empirical orthogonal functions for improved irrigation water management

Abstract: Precision agriculture offers the technologies to manage for infield variability and incorporate variability into irrigation management decisions. The major limitation of this technology often lies in the reconciliation of disparate data sources and the generation of irrigation prescription maps. Here the authors explore the utility of the cosmic-ray neutron probe (CRNP) which measures volumetric soil water content (SWC) in the top ~ 30 cm of the soil profile. The key advantages of CRNP is that the sensor is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Another option is to delineate zones based on soil texture using apparent electrical conductivity (EC a ) maps Zhao et al, 2017) or other hydrogeophysical datasets (Finkenbiner et al, 2018). However, caution must be exercised to determine whether variabilities indicated by EC a maps are due to soil texture, topography, or other differences (Sudduth et al, 2001).…”
Section: Advancesmentioning
confidence: 99%
“…Another option is to delineate zones based on soil texture using apparent electrical conductivity (EC a ) maps Zhao et al, 2017) or other hydrogeophysical datasets (Finkenbiner et al, 2018). However, caution must be exercised to determine whether variabilities indicated by EC a maps are due to soil texture, topography, or other differences (Sudduth et al, 2001).…”
Section: Advancesmentioning
confidence: 99%
“…Zreda et al, 2008Zreda et al, , 2012Desilets et al, 2010;Franz et al, 2015;Kohli et al, 2015;Andreasen et al, 2017). Several studies have used CRNS data to support precision agriculture (Finkenbiner et al, 2019), catchment hydrology (Fersch et al, 2018), snow hydrology (Schattan et al, 2017), land surface modeling (Rosolem et al, 2014;Baatz et al, 2017;Lawston et al, 2017), validation of remote sensing products (Montzka et al, 2017;Babaeian et al, 2018), and understanding vegetation dynamics (Franz et al, 2013). In order to maximize the societal and scientific relevance of SWC data (Vereecken et al, 2008), practical value-added products need to be developed that can estimate both water flux and root zone SWC changes.…”
Section: Introductionmentioning
confidence: 99%
“…Few recent studies have focused on the use of CRNP data for the estimation of SHPs with promising results. Both Finkenbiner et al (2018) and Gibson and Franz (2018) combined CRNP data with empirical orthogonal functions to isolate spatial patterns of SHPs in selected agricultural fields. A statistical analysis confirmed that the use of CRNP data can improve the estimate of SHPs at the field scale.…”
mentioning
confidence: 99%